Sleep Hygiene and Sleep Quality of Third‐Trimester Pregnant Women. Issue 1 (9th December 2015) - Tsai, Shao‐Yu; Lee, Chien‐Nan; Wu, Wei‐Wen; Landis, Carol A.
Abstract: The purpose of this descriptive study was to examine the associations of sleep hygiene and actigraphy measures of sleep with self‐reported sleep quality in 197 pregnant women in northern Taiwan. Third‐trimester pregnant women completed the Sleep Hygiene Practice Scale (SHPS) and the Pittsburgh Sleep Quality Index (PSQI) as well as the Center for Epidemiologic Studies‐Depression Scale (CES‐D), and wore an actigraph for 7 consecutive days. Student's t ‐test was used to compare the SHPS scores and means as well as variability of actigraphy sleep variables between poor sleepers (i.e., PSQI global score >5) and good sleepers (i.e., PSQI global score ≤5). Compared to good sleepers, poor sleepers reported significantly worse sleep hygiene, with higher SHPS scores and higher sleep schedule, arousal‐related behavior, and sleep environment subscale scores. Poor sleepers had significantly greater intra‐individual variability of sleep onset latency, total nighttime sleep, and wake after sleep onset than good sleepers. In stepwise linear regression, older maternal age ( p = .01), fewer employment hours per week ( p = .01), higher CES‐D total score ( p < .01), and higher SHPS arousal‐related behavior subscale scores ( p < .01) predicted self‐reported global sleep quality. Findings support avoiding physically, physiologically, emotionally, or cognitively arousing activities before bedtime as a target for sleep‐hygiene intervention in women during pregnancy. © 2015 Wiley Periodicals, Inc.